DETERMINANTS OF ASPHYXIA NEONATORUM IN Dr. M. YUNUS HOSPITAL BENGKULU - Lusi Andriani; Rigita Tiya Nora Nika; Dwie Yunita Baska; Epti Yorita; Else Tri Rahayu (Poltekkes Kemenkes Bengkulu, 2022)
Asphyxia is one of the causes of neonatal death. The causes of asphyxia neonatorum consist of maternal factors, placental factors, fetal factors and labor factors. The purpose of this study was to determine the determinants of the incidence of asphyxia neonatorum in Dr. M. Yunus hospital Bengkulu. Design of this study uses a case control study with a retrospective approach. The population in this study were all newborns recorded in the perinatology room register at Dr. M. Yunus hospital Bengkulu in 2020 and 2021, as many as 577 newborns. The case sample in the case sampling technique was total sampling with a total of 186 newborns with asphyxia. The control sample was taken with a ratio of 1:1 so that the control sample was 186 newborns who did not have asphyxia. The results of statistical tests showed that maternal age, amniotic fluid mixed meconium, prolonged labor and type of delivery with p value <0.05, which means that there are a relationship with the incidence of asphyxia in newborns. The results of statistical tests on breech position and placenta previa showed p value >0.05, which means that there are no relationship to the incidence of asphyxia in newborns. The most influential factor with the incidence of asphyxia was amniotic fluid mixed meconium with an OR value of 3.798. It is necessary to increase the ability of midwives in providing services and delivery assistance, especially in the event of amniotic fluid mixed meconium through education and training both internally and externally through seminars or special training.